2004
DOI: 10.1037/0021-9010.89.4.599
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Personality and Perceptions of the Work Situation on Workplace Deviance.

Abstract: Previous research on workplace deviance has examined the relationship of either personality or employees' situational perceptions with deviant behavior. In this study, the authors focused on the joint relationship of personality and perceptions of the work situation with deviant behavior. Using 4 samples of employees and multiple operationalizations of the core constructs, the authors found support for the hypothesis that positive perceptions of the work situation are negatively related to workplace deviance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
332
2
12

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 448 publications
(370 citation statements)
references
References 45 publications
(76 reference statements)
24
332
2
12
Order By: Relevance
“…However, our findings also support the assertion of Colbert, Mount, Harter, Witt, and Barrick (2004) that "the norm of reciprocity should be modified to include the role of personality" (p. 607). Colbert and colleagues found that perceived organizational support was negatively associated with interpersonal deviance for individuals low in agreeableness but not for individuals high in agreeableness.…”
Section: Individual Differences and Justice Perceptions Jointly Predisupporting
confidence: 85%
“…However, our findings also support the assertion of Colbert, Mount, Harter, Witt, and Barrick (2004) that "the norm of reciprocity should be modified to include the role of personality" (p. 607). Colbert and colleagues found that perceived organizational support was negatively associated with interpersonal deviance for individuals low in agreeableness but not for individuals high in agreeableness.…”
Section: Individual Differences and Justice Perceptions Jointly Predisupporting
confidence: 85%
“…There is a general agreement that among the five factors, conscientiousness is the most predictive factor of job performance, followed by emotional stability (Hurtz & Donovan, 2000). Job performance has been measured in direct and indirect ways, among them absenteeism (Judge et al 1997), deviant behavior (Colbert et al 2004), occupational safety (Clarke and Robertson, 2005) and, sometimes, job satisfaction (Judge et al 2002). Evidence on the influence of the relationship between personality characteristics and specific work environments on performance is found in Hurtz and Donovan (2000).…”
Section: Introductionmentioning
confidence: 97%
“…First, it is a response to the call for more research on psychological factors that may serve as mediators, moderators, or even antidotes to deviant behavior and their effects (Colbert et al, 2004;Robinson & Bennett, 1995). Second, given that psychological factors and individual differences variables are central to most models of deviant employee behavior (Judge, Scott, & Ilies, 2006), it is important to examine the direct and mediating effects of psychological factors in a single study.…”
Section: The Aim Of This Studymentioning
confidence: 99%
“…Workplace deviance has become the focus of an increasing number of research studies (e.g., Colbert, Mount, Harter, Witt, & Barrick, 2004;Sackett & DeVore, 2001). Workplace deviance is defined as "voluntary behavior that violates significant organizational norms and in so doing threatens the well-being of an organization, its members, or both" (Robinson & Bennett, 1995:556).…”
Section: Introductionmentioning
confidence: 99%